Morphological Aspects of Bismuth Sulpho Iodide Grown by Silica Gel Technique - Kumara Raman, S. (Asian Journal of Chemistry, 2012)
Bismuth sulpho iodide (BiSI) has been prepared by the reaction of BiCl3 dissolved in H2SO4 and acetic acid in silica gel. The morphology of some as-grown symmetrical crystals has been studied by optical microscopy. The growth morphology studies indicate that the grown crystals are needle-shaped, orthorhombic disphenoidal. The growth mechanism has been assessed.